2015
DOI: 10.1179/2042618615y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic manual therapy in the management of non-specific shoulder pain: a systematic review

Abstract: Objectives: Non-specific shoulder pain (NSSP) is often persistent and disabling leading to high socioeconomic costs. Cervical manipulation has demonstrated improvements in patients with NSSP, although risks associated with thrust techniques are documented. Thoracic manual therapy (TMT) may utilise similar neurophysiological effects with less risk. The current evidence for TMT in treating NSSP is limited to systematic reviews of manual therapy (MT) applied to the upper quadrant. These reviews included trials th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
0
23
0
2
Order By: Relevance
“…Wassinger et al 76 found that manual therapy directed at the cervicothoracic region acutely increased pressure pain thresholds and decreased pain in individuals with experimentally induced shoulder pain. In a recent systematic review, Peek et al 54 reported that thoracic manual therapy accelerated recovery and reduced pain and disability in individuals with shoulder pain immediately and for up to 1 year when compared to usual care. They concluded that further, high-quality randomized controlled trials (RCTs) should be conducted to investigate the effect of thoracic manual therapy for the treatment of shoulder pain.…”
Section: T T Conclusion: Adding 2 Sessions Of High-dosementioning
confidence: 99%
“…Wassinger et al 76 found that manual therapy directed at the cervicothoracic region acutely increased pressure pain thresholds and decreased pain in individuals with experimentally induced shoulder pain. In a recent systematic review, Peek et al 54 reported that thoracic manual therapy accelerated recovery and reduced pain and disability in individuals with shoulder pain immediately and for up to 1 year when compared to usual care. They concluded that further, high-quality randomized controlled trials (RCTs) should be conducted to investigate the effect of thoracic manual therapy for the treatment of shoulder pain.…”
Section: T T Conclusion: Adding 2 Sessions Of High-dosementioning
confidence: 99%
“…The second high-quality SR assessed thoracic MT (TMT). 43 Three RCTs met the eligibility criteria of this SR. All 3 used usual care as a comparison (ie, general practitioner's advice, steroid injections, or PT). This SR concluded that TMT helped accelerate recovery and reduced pain outcomes and disability measures immediately and for up to 52 weeks compared with usual care.…”
Section: Nonspecific Spmentioning
confidence: 99%
“…Several conservative treatments have been advocated, including analgesics, nonsteroidal anti-inflammatory drugs, steroids, active physiotherapy, and health education [6]. Due to poor agreement on diagnostic criteria and the lack of specificity of clinical assessment that is considered a "gold standard", no uniform, specific treatment protocol exists [7,8]. Acupuncture, as a complementary alternative treatment, has been used in the treatment for CSP in China and has been also accepted for pain management in Western medicine [9].…”
Section: Introductionmentioning
confidence: 99%